Carbon Sequestration and the Enzymic Latch Mechanism in Red, Black and White Mangrove Soils of Florida USA. - Dasat, G. S. (European Journal of Applied Sciences, 2024)
pMangrove swamps are important habitat types providing vital ecological services, such as protection of coastlines from erosion and extreme weather conditions including hurricanes, recycling of nutrients and sequestration of carbon. Mangrove swamps support a wide range of biodiversity, improve water quality, provide fish for local communities. They are also used as a source of wood fuel, medication as well as for harvesting honey for the local population. Soil samples for laboratory analyses were collected from red (emRhizophora mangle/em), black (emAvicennia germinans/em) and white (emLaguncularia racemose/em) mangroves in Florida, USA to determine the biogeochemistry processes. Results of analyses indicated that the red mangrove soil is the most efficient for carbon sequestration. It had the lowest phenol oxidase activity (206.15 nmol dicq gsup-1/sup hsup-1/sup), highest phenolic concentration (262.33 µg gsup-1/sup) and lowest hydrolase enzyme activity (β-glucosidase) (3.04 nmol gsup-1/sup minsup-1/sup) and, as a result, the highest concentration of soil organic matter (SOM) (57.9%). It is believed that the high soil water content (84.2%).) of the red mangrove, due to its proximity to the sea, is a key driver of these observations. The 'enzymic latch' mechanism appears to be prevalent in the red mangrove soil, in particular, allowing these ecosystems to be effective at carbon storage hence, could serve as an important natural tool in mitigating the effect of climate change. nbsp;Preservation and conservation of mangrove swamps is vital in balancing the effect of global warming./p